2020
DOI: 10.5267/j.msl.2019.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Marketing performance as implication of brand image mediated by trust

Abstract: Research on marketing performance has been discussed by several previous researchers on institutions and industries. One of them is in the field of education. The purpose of this study is to analyze the effect of brand image toward marketing performance, brand image on trust and brand image toward marketing performance mediated by trust. In previous studies there have been many studies that measure marketing performance from internal or management perspective. On the other hand, this research discusses marketi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 12 publications
1
11
0
2
Order By: Relevance
“…At this stage, the importance of brands is revealed once again. Brand image has a significant effect on trust (Alamsyah et al, 2020;Propheto et al, 2020); an environmentally sensitive image is likely to increase trust in the business. Brand image is the evaluation of the interaction with the brand (Veloutsou, 2015).…”
Section: Environmental Attitudes and Trustmentioning
confidence: 99%
“…At this stage, the importance of brands is revealed once again. Brand image has a significant effect on trust (Alamsyah et al, 2020;Propheto et al, 2020); an environmentally sensitive image is likely to increase trust in the business. Brand image is the evaluation of the interaction with the brand (Veloutsou, 2015).…”
Section: Environmental Attitudes and Trustmentioning
confidence: 99%
“…Mishra et al (2014) found that the implementation of a consumer relationship management strategy has a positive effect on an organization's image. The image of an organization allows its offer to be implanted in the minds of consumers (Propheto et al, 2020). Vesal et al (2020) point out that a favorable image enables the organization to gain a strong market position and stand out from the competition.…”
Section: Knowledge Managementmentioning
confidence: 99%
“…The company that enjoys the image of a good brand achieves a strong competitive advantage as consumers chose the products of that company after comparing it with the products of other companies (CHA & LYU, 2019) The importance of The Brand Image also comes from its ability to distinguish and position the company in a privileged position in the market. A variety of brand images can reflect a customer's view of a particular product and also the manufacturer of that product (Propheto et al, 2020). A strong mental image of the brand means a long history, richness, and a higher degree of the brand on the common use and consumption and the ability to face competition all this enables the brand to form a distinct structure and identity.…”
Section: The Moderating Role Of Brand Imagementioning
confidence: 99%